2008
DOI: 10.1177/1534735407313395
|View full text |Cite
|
Sign up to set email alerts
|

Using Mixed Methods for Evaluating an Integrative Approach to Cancer Care: A Case Study

Abstract: Objective. To evaluate the impact of participating in an integrative cancer care program at the Centre for Integrated Healing in Vancouver, British Columbia, on patients' lifestyle, quality of life, and overall well-being. Study Design. A mixed-methods case study with a pre- and posttest design. No control group was utilized. Methods. All new patients starting at the Centre for Integrated Healing between May and September of 2004 were invited to join the study. Forty-six of 77 new patients agreed to participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
0
23
1
Order By: Relevance
“…Built Environment ( (Brailsford, Lattimer et al 2004;Cavana et al 1999;Dangerfield 1999;Gary and Larsen 2000;Gonzalez-Busto and Garcia 1999;Lane and Husemann 2008a;Lane et al 2000;Taylor and Dangerfield 2005;van Ackere and Smith 1999;Wolstenholme 1999a) Environment, agriculture (Bene and Doyen 2000;Cavana et al 1996;Janssen 1999;Janssen and De Vries 2000;Noble and Walker 2006;Stave 2002;van Vuuren et al 1999;Yu et al 2003;Zhang and Mitsch 2005) Supply chain, production, projects (Ackermann, Eden et al 1997;Dangerfield and Roberts 2000;Fung 1999;Howick and Eden 2001;Kleijnen and Smits 2003;McCray and Clark 1999;Riddalls et al 2000;Rodrigues and Williams 1998;Spengler and Schroter 2003;Williams, Ackermann et al 2003b;Williams 1999b;Zhou et al 2006) Other applications Table 3 Applications of system dynamics Health (Angelis, Pavlopoulos et al 1998;Brazier et al 2008;Fahey et al 2004;Gregory and Midgley 2000;Hindle et al 1998;Kotiadis and Mingers 2006a;…”
Section: Discussionmentioning
confidence: 99%
“…Built Environment ( (Brailsford, Lattimer et al 2004;Cavana et al 1999;Dangerfield 1999;Gary and Larsen 2000;Gonzalez-Busto and Garcia 1999;Lane and Husemann 2008a;Lane et al 2000;Taylor and Dangerfield 2005;van Ackere and Smith 1999;Wolstenholme 1999a) Environment, agriculture (Bene and Doyen 2000;Cavana et al 1996;Janssen 1999;Janssen and De Vries 2000;Noble and Walker 2006;Stave 2002;van Vuuren et al 1999;Yu et al 2003;Zhang and Mitsch 2005) Supply chain, production, projects (Ackermann, Eden et al 1997;Dangerfield and Roberts 2000;Fung 1999;Howick and Eden 2001;Kleijnen and Smits 2003;McCray and Clark 1999;Riddalls et al 2000;Rodrigues and Williams 1998;Spengler and Schroter 2003;Williams, Ackermann et al 2003b;Williams 1999b;Zhou et al 2006) Other applications Table 3 Applications of system dynamics Health (Angelis, Pavlopoulos et al 1998;Brazier et al 2008;Fahey et al 2004;Gregory and Midgley 2000;Hindle et al 1998;Kotiadis and Mingers 2006a;…”
Section: Discussionmentioning
confidence: 99%
“…One study of patients taking part in an integrative cancer treatment reported no significant changes in quantitative measures of patient well-being. 21 However, the same study found improvements in qualitative measures, including personal growth and enhanced awareness of living in the moment, led to greater acceptance of the cancer experience. 21 This suggests that the experience of having cancer may evoke spiritual needs in individuals that prompt them to seek CAM treatment to cope with the uncertainty of the present and future.…”
Section: Introductionmentioning
confidence: 99%
“…The description and interpretation is done without reconfiguring it into a more highly interpretive form. Instead, findings were made to stay closer to the words of the interviewees and described their experience, while at the same time capturing the meaning they attributed to this experience (Brazier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The interpretive description qualitative approach (Thorne et al, 1997;Brazier, Cooke & Moravan, 2008) was used to analyze the scripts generated from the interviews. Using this approach, the experiences of the interviewees in relation to how actions in the work environment constrained the implementation and internalization of the ten management practices in the organization is described and interpreted.…”
Section: Discussionmentioning
confidence: 99%